PERILAKU AGRESIF YANG DIALAMI KORBAN KEKERASAN DALAM PACARAN - Khaninah, Anik Nur; Widjanarko, M. (Faculty of Psychology, Diponegoro University, 2016)
The objective of this study is to determine the forms of aggressive behavior that received by victims of courtship violence and the factors that causes violence in long term courtship. The method used in this study is a qualitative research method with a phenomenological approach using data collection techniques by observing and interviewing. The sampling technique used in this study is snowball technique. Data analysis techniques follow this stages: analyzing all the data, categorizing data, preparing the psychological dynamics, connecting with the theoretical basis and drawing conclusions. Based on the results of the study, it shows the forms of aggressive behavior that received by victims of violence in courtship is verbal or symbolic aggression behavior, such as harsh words, words that is not worth to listen, mocking/scolding, threatening, insisting, and limiting intercommunication. In case of violation of property rights, is the property of the subjects used at one’s pleasure by their mate without permission. Physical assault is in the form of forced asking or confiscated subject as well as hitting or knocking head. While the reason for the victims to survive is feeling shy because everyone already knows their courtship relationship.Besides, the victim thinks and hopes theirmatewould be better and their relationshipwould be improved.